2007
DOI: 10.1186/1471-2474-8-60
|View full text |Cite
|
Sign up to set email alerts
|

50 years experience with Dupuytren's contracture in the Erlangen University Hospital – A retrospective analysis of 2919 operated hands from 1956 to 2006

Abstract: Background: Dupuytren's disease (DD) is a hand disorder mainly among the northern population. In contrast it is rare in the mediterranean population. Therefore typical habits and dietetic influences have been discussed as well as genetic predisposition. Still, since the first description by Dupuytren in 1834 only little is known about the etiology and pathogenesis of this disease. Some hints were found for a higher prevalence among people with diabetes, alcohol abuse or smoking. Also, intensive manual work or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
3
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(73 citation statements)
references
References 42 publications
(66 reference statements)
3
62
3
5
Order By: Relevance
“…In the prayer sign test, where the palms of the hands are placed against each other, the early lesions in either hand are magnified compared with when each hand is placed separately on a table for the table test. In our study, LJM is associated with poor glycemic control and macrovascular complications which is associated with increased risks of developing LMJ by 2.2 times, and with manual labour since diabetic patients who were manual labourer had greater chance to develop LMJ by 7.7 times compared to non-manual laborers, this finding is in line with those reported by other authors, 17 regarding the gender being female was associated with increased risk of developing LJM. Dupuytren's contracture has been reported in (16%) of diabetic patients compared to controls with a prevalence of (2%).…”
Section: Data Management and Statistical Analysissupporting
confidence: 92%
“…In the prayer sign test, where the palms of the hands are placed against each other, the early lesions in either hand are magnified compared with when each hand is placed separately on a table for the table test. In our study, LJM is associated with poor glycemic control and macrovascular complications which is associated with increased risks of developing LMJ by 2.2 times, and with manual labour since diabetic patients who were manual labourer had greater chance to develop LMJ by 7.7 times compared to non-manual laborers, this finding is in line with those reported by other authors, 17 regarding the gender being female was associated with increased risk of developing LJM. Dupuytren's contracture has been reported in (16%) of diabetic patients compared to controls with a prevalence of (2%).…”
Section: Data Management and Statistical Analysissupporting
confidence: 92%
“…5 and 6). The relevance of some of the many implicated etiological factors such as alcohol abuse, cirrhosis of the liver, smoking, epilepsy, diabetes mellitus, and hypercholesterolemia on the prevalence of DD is questioned [17,57,92].…”
Section: Significance Of Associated Risk Factors and Prevalence Of Ddmentioning
confidence: 99%
“…28 However, more recent studies in the UK and Germany have reported almost equal involvement of both hands. 30 …”
Section: Epidemiology and Prognosismentioning
confidence: 99%